Pemasaran digital dengan memanfaatkan landing page pada perusahaan start-up - Angga Febrian; Lia Febria Lina; Vera Apri Dina Safitri; Agus Mulyanto (University of Islam Malang, 2021)
The increasing use of social media such as Instagram and Facebook can be utilized to reach a wider and more targeted consumer by creating the right content organically (free of charge), and doing paid advertising on these platforms. However, his lack of knowledge about how to make real content and paid advertising is an obstacle for marketers to take advantage of it. So that we need the right strategy in marketing products through these media. The marketer's job is to increase the number of followers on social media and customer interactions because there is a positive relationship between the number of followers and sales. This training aims to help startups in Lampung to maximize the use of social media, in this case, we provide training in creating landing pages and financial preparation training. Partners in this activity are sharia motorcycle taxi transportation companies (OJESA). In the end, this activity can be beneficial for partners by increasing knowledge about digital marketing by utilizing landing pages in advertising and managing finances. Partners can use the facilities provided by the platform in advertising. As well as understanding effective and efficient advertising tactics and strategies.